PENGARUH KOMUNIKASI KEPEMIMPINAN DEPARTEMEN HUMAN RESOURCES TERHADAP KEPUASAN KERJA KARYAWAN THE WESTIN JAKARTA - Haryanto Haryanto; Rita Rita (ITB Swadharma, 2020)
The influence of communication on the leadership of the human resources department on job satisfaction of employees of the westin Jakarta. In good communication, the role of a leader is needed. Good leadership and proper communication methods are also factors that affect employee job satisfaction. This study aims to (1) determine whether the process of leadership communication affects employee job satisfaction; (2) Knowing whether the message in leadership communication affects employee job satisfaction; (3) Knowing whether the relationship factor in communication has an influence on employee job satisfaction. This research uses quantitative research. The sample in this study were employees from the westin Jakarta who were taken as many as 67 respondents with proportional stratified random sampling technique. The instruments used in this study were observation and questionnaires. Data analysis used multiple linear regression with the help of SPSS 22.0. The results showed that (1) the process of leadership communication partially had no effect on job satisfaction at the Westin Jakarta human resources. (2) The process, messages and relationships simultaneously had an effect on job decision for employees of Westin Jakarta Human Resources.